Walt Disney's Ksiega dzungli - Gorska, Danuta; Kipling, Rudyard, 1865-1936.; Walt Disney Productions (Warszawa [Poland] : Egmont American, 1993)
The animal friends of the boy raised by wolves escort him out of the jungle to keep him safe from the tiger who seeks to kill him. For ages 4-9.
Translation of: Walt Disney's jungle book.
Based on "The jungle book" by Rudyard Kipling.
Keywords: Jungles -- Juvenile fiction; Animals -- Juvenile fiction